Neglected Effects of Inoculum Preservation on the Start-Up of Psychrophilic Bioelectrochemical Systems and Shaping Bacterial Communities at Low Temperature - Lu, Sidan; Xie, Binghan; Liu, Bingfeng; Lu, Baiyun; Xing, Defeng (Frontiers in Microbiology, 2019)
Bioelectrochemical systems (BESs) are capable of simultaneous wastewater treatment and resource recovery at low temperatures. However, the direct enrichment of psychrophilic and electroactive biofilms in BESs at 4 °C is difficult due to the lack of understanding in the physioecology of psychrophilic exoelectrogens. Here we report the start-up and operation of microbial fuel cells (MFCs) at 4 °C with pre-acclimated inocula at different temperatures (4 °C, 10 °C, 25 °C, and -20 °C) for 7 days and 14 days. MFCs with 7 d-pretreated inocula reached higher peak voltages than did those with 14 d-pretreated inocula. The highest power densities were obtained by MFCs with 25 °C – 7 d, 25 °C – 14 d, and 4 °C – 7 d pretreated inocula (650-700 mW/m2). In contrast, the control MFCs with untreated inocula were stable at 450 mW/m2. The power densities of MFCs with 7 d-pretreated inocula were higher than those obtained by MFCs with 14 d-pretreated inocula. The MFCs with 10 °C – 7 d-pretreated inocula and the control MFCs showed higher chemical oxygen demand (COD) removal (90%-91%) than other MFCs. 454 pyrosequencing based on 16S rRNA gene amplicons indicated that bacterial communities of the anode biofilms were shaped by pretreated inocula at different temperatures. Compared with the control MFCs with untreated inocula, MFCs with temperature-pretreated inocula demonstrated higher microbial diversity, but did not do so with -20 °C-pretreated inocula. Principal components analysis (PCA) revealed an obvious separation between the inocula pretreated at 4 °C and those pretreated at 10 °C, implying that bacterial community structures could be shaped by pretreated inocula at low temperatures. The pretreatment period also had a diverse impact on the abundance of exoelectrogens and non-exoelectrogens in MFCs with inocula pretreated at different temperatures. The majority of the predominant population was affiliated with Geobacter with a relative abundance of 17-70% at different pre-acclimated temperatures, suggesting that the exoelectrogenic Geobacter could be effectively enriched at 4 °C even with inocula pretreated at different temperatures. This study provides a strategy that was previously neglected for fast enrichment of psychrophilic exoelectrogens in BESs at low temperatures.